Haemodynamic forces as predictors of cardiac remodelling and outcome in heart failure with reduced ejection fraction treated with sacubitril/valsartan. (3rd October 2022) - Fabiani, I; Pugliese, N R; Castiglione, V; Pedrizzetti, G; Tonti, G; Chubuchny, V; Becherini, F; Taddei, C; Gimelli, A; Del Punta, L; Balletti, A; Masi, S; et al.
Abstract: Background: Angiotensin receptor-neprilysin inhibitor (ARNI) is a cornerstone of treatment in heart failure (HF) with reduced ejection fraction (HFrEF), but its effectiveness shows interindividual differences. Objectives: To evaluate the predictive value of echo-derived hemodynamic forces (HDF), together with other echocardiographic, biohumoral and cardiopulmonary parameters on a) response to ARNI after 6 months; b) adverse cardiovascular events at follow-up. Methods: Eighty-nine consecutive HFrEF patients from two HF centers performed clinical evaluation, laboratory analyses, rest echocardiography and cardiopulmonary exercise testing. Response to ARNI at 6 months was considered in patients without HF admissions, death, or urgent heart transplant and with a ≥50% reduction in NT-proBNP levels and/or ≥10% increase in left ventricle ejection fraction. After 6 months, patients were followed up for a composite endpoint of cardiovascular death, HF-related hospitalization and new-onset atrial fibrillation. Results: Response to ARNI was documented in 45/89 (51%) of patients. At baseline, responders and non-responders were paired in clinical assessment, conventional echocardiography, functional status and therapy. At multivariate logistic regression analysis, HDF-derived whole cardiac cycle left ventricle strength (wLVS) was the only independent predictor of ARNI response at 6 months (odds ratio 1.36, 95% confidence interval 1.10–1.67; p=0.004). A wLVS ≥3.7% showed a good accuracy in predicting ARNI response (AUC = 0.736, 0.607–0.840; p<0.0001). During a median of 33 (IQR 23–41) months, wLVS increase from baseline to 6-month (ΔwLVS) showed a high discrimination ability at time-dependent ROC analysis (optimal cut-off: ≤0.5%; AUC=0.811, 0.69–0.90; p<0.0001), stratified prognosis at Kaplan-Meier analysis (log-rank p<0.0001), and remained an independent prognostic predictor of the composite endpoint (hazard ratio 0.76, 0.61–0.95; p<0.01) even after adjusting for clinical, functional and conventional echocardiographic parameters. Conclusions: HDF analysis may help predict ARNI response and optimize follow-up and medical/device strategies in patients with HfrEF. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Fondazione Toscana Gabriele Monasterio, Pisa, Italy